Digital Cash Flow Management for MSMEs: Development and Assessment of a Mobile Financial Monitoring Tool in Cebu City - Estreba, Alvin (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study developed and assessed a mobile cash flow management tool for micro, small, and medium enterprises (MSMEs) in Barangay Tisa, Cebu City. The study was anchored on the Unified Theory of Acceptance and Use of Technology (UTAUT) and Garvin’s Dimensions of Quality. It used a quantitative descriptive research design, with an adapted questionnaire as the main instrument. The respondents consisted of 30 MSM entrepreneurs, 30 selected BSBA students, 10 cash flow management experts, and 10 information technology experts, for a total of 80 respondents. Data were analyzed using percentage, weighted mean, and one-way ANOVA. Results showed that the tool, “Budyet ta Bai,” was developed to support cash inflow and outflow recording, expense tracking, budgeting, reporting, transaction categorization, and financial monitoring through smartphones. The tool was rated to a very great extent in performance, accuracy, reliability, serviceability, and portability. It was also rated highly acceptable in terms of performance expectancy, effort expectancy, and social influence. Identified adoption barriers included technological limitations, resistance to change, trust and security concerns, device compatibility, cost, affordability, and limited financial literacy. The study concluded that the mobile tool can help MSMEs and students improve cash monitoring, financial tracking, and decision-making. It recommended adoption of the tool and continuous monitoring for further functional improvement. The study aligns with SDG 4, SDG 8, SDG 9, SDG 11, SDG 16, and SDG 17 by supporting financial education, MSME growth, innovation, local enterprise resilience, responsible governance, and collaboration. Its sustainability impact is mainly socio-economic, technological, educational, institutional, and community-based because it strengthens MSME cash management and promotes practical digital financial practices.
Keywords: Cash Flow Management; Digitalization; Financial Monitoring; Mobile Tool; MSMEs; Sustainability; Technology Adoption